Men Vote in Mars, Women Vote in Venus: A Survey Experiment in the Field - Vincenzo Galasso; Tommaso Nannicini (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper investigates the differential response of male and female voters to competitive persuasion in political campaigns. During the 2011 municipal elections in Milan, a sample of eligible voters was randomly divided into three groups. Two were exposed to the same incumbent's campaign but to different opponent's campaigns, with either a positive or a negative tone. The third control group received no electoral information. The campaigns were administered online and consisted of a bundle of advertising tools (videos, texts, slogans). Stark gender differences emerge. Negative advertising increases men's turnout, but has no effect on women. Females, however, vote more for the opponent and less for the incumbent when they are exposed to the opponent's positive campaign. Exactly the opposite occurs for males. Additional tests show that our results are not driven by gender identification with the candidate, ideology, or other voter's observable attributes. Effective strategies of persuasive communication should thus take gender into account. Our results may also help to reconcile the conflicting evidence on the effect of negative vs. positive advertising, as the average impact may wash out when aggregated across gender.
Keywords: D72; J16; M37; 330; gender differences; political campaigns; competitive persuasion